الأغنية والصور لتعليم المفردات في المدرسة الابتدائية - Matin, Iman; Larenzi, Annisa Hanin; Arifin, Syamsul (Kalimatuna: Journal of Arabic Research, 2022)
This research is based on the problems students faced in learning Arabic vocabulary. This research aims to reveal the conduct of instructional vocabulary among students, knowing the students' ability to comprehend vocabulary, and revealing the results of instructional vocabulary after using the song and pictures. The researchers used experimental research method with a quantitative approach. The researchers prepared the pre-test and the post-test to collect data. After processing and analyzing the data, the researchers obtained the mean group of the students' post-test results, 50 in the experimental group and 74 in the control group. The evidence found shows that the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. This means that the use of song and pictures in the process of teaching and learning vocabulary has a strong impact. The process of teaching and learning vocabulary using song and pictures among students has a strong impact on vocabulary comprehension.